From landscape description to quantification: A new generation of reconstructions provides new perspectives on Holocene regional landscapes of SE Sweden. (January 2015) - Åkesson, Christine; Nielsen, Anne Birgitte; Broström, Anna; Persson, Thomas; Gaillard, Marie-José; Berglund, Björn E
The development since the beginning of the 20th century of the pollen-analytical theory and method as a palaeoecological tool for describing landscape development is outlined with reference to southern Scandinavia. Numerical methods applied since the 1980s are discussed. The aim of this paper is to provide a new perspective on the landscape development and human impact during the Holocene by applying the Regional Estimates of VEgetation Abundance from Large Sites (REVEALS) model to the pollen records from the reference site Lake Färskesjön in SE Sweden. The model was applied both to a previously published record (core 1956, entire Holocene until ad 1600) and a newly collected dataset (core 2013, the last 3000 years). The comparison between the REVEALS estimates of vegetation cover and historical landscape maps indicate that traditional, uncorrected pollen percentages significantly underestimate the degree of landscape openness created by long-term farming and pasturing, but that the degree of underestimation varies over time, depending on the species composition of both the forest and the open-land communities. The REVEALS reconstructions are also a useful tool for the quantification of past land-use changes that may have affected the nutrient loading to the Baltic Sea.